Circularly Polarized Cylindrical Dielectric Resonator Antenna with Different Shapes Cross Slot - Zahra Rahimian (Institute of Advanced Engineering and Science, 2014)
A cross slot coupled cylindrical dielectric resonator antenna (CDRA) operating in the X-band (8GHz -12GHz) frequency range is studied. The proposed CP designs are achieved by implementing a suitable cross slot on the ground plane (in the case of aperture coupled feed method), which results in excitation of two near degenerate orthogonal modes of near equal amplitudes and 90°phase difference. Attempts are made to change the geometry of slots ends to introduce a novel structure in order to achieve a better impedance bandwidth with an improved 3dB axial ratio (AR) bandwidth. It is found that the hourglass of cross slot has a great effect on the strength of coupling between the feed line and the dielectric resonator antenna. In simulation an impedance bandwidth of 46.15% and axial ratio bandwidth of 22% has been achieved with the above geometry. An improvement of 12% in impedance bandwidth and 11.2% in Axial ratio bandwidth is obtained over conventional rectangular cross slot.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6484